Impact of AQP-5 on the growth of colorectal cancer cells and the underlying mechanism - Shan, Tao (Int J Clin Exp Pathol, 2018)
Aquaporin 5 (AQP-5) is highly expressed in colorectal cancer tissue and associated with colorectal cancer development and prognosis. Here, we explored the effects of AQP-5 on colorectal cancer cell proliferation and apoptosis and the underlying mechanism by inhibiting endogenous AQP-5 expression in the human colorectal cancer cell lines COLO 205 and SW480. These cells were transfected with an AQP-5-siRNA, and transfection efficiency and its effects on AQP-5 expression were assessed by immunofluorescence and PCR, respectively. Then, cell proliferation was assessed via the MTT assay, apoptosis was assessed by Annexin V-FITC/PI and TUNEL assays, and expression changes in Bax and Bcl-2 were assessed by RT-PCR and western blotting. Transfection with AQP-5-siRNA reduced AQP-5 expression by up to 62%. The MTT assay showed that cell proliferation was significantly inhibited by AQP-5-siRNA transfection compared to that in NS-siRNA-transfected cells (P < 0.05). Flow cytometry analysis revealed that the percentage of apoptotic AQP-5-siRNA-transfected cells was significantly higher than that of NS-siRNA-transfected cells (P < 0.05). Real-time quantitative RT-PCR and western blotting showed that AQP-5-siRNA significantly increased the Bax/Bcl-2 mRNA and protein ratios compared with those following NS-siRNA transfection. Thus, AQP5-siRNA promotes apoptosis of colorectal cancer cells, which may be associated with Bax/Bcl expression.